3 - Le pastoralisme transfrontalier et le droit à la nationalité : quelles perspectives en Afrique de l’Ouest ? - Diop, Abdou Khadre (African Sociological Review, 2023)
The issue of the right to nationality, described by Hannah Arendt as “the right to have rights”, and the eradication of statelessness remains of international concern. Conventions have been adopted and signed in this regard. However, a specific issue is at stake in Africa and requires “an African gaze”: cross-border pastoralism related to the right to nationality. Nomadic pastoralism and migratory stock farming are a production system of livelihood and a way of life for millions of people in West Africa. This mobility with livestock herds in search of water and pasture may take place within national territories or cross borders. It gathers several ethnic groups historically associated with pastoralism, in particular the Tuareg (Berber/Amazigh) and the Fulani, including Fulani subgroups such as the Mborobo. The arbitrary drawing of West African borders has imposed a legal barrier to pastoralist groups, and the postcolonial state has accentuated this disruption. Attempts to encourage nomadic or transhumant pastoralists to settle or acknowledge a centralized political authority has created tensions during colonial and postcolonial eras. This paper seeks to demonstrate that our legal framework and public policy are irrelevant: we should rebuild basic paradigms and reverse the Eurocentric vision of law to adapt legal framework and public policies to the needs of pastoralist communities, to empower them, to reduce their vulnerability and to facilitate their permanent mobility.